EFISIENSI PRODUKSI SAPI POTONG PADA PETERNAKAN RAKYAT PADA MUSIM KEMARAU DI DAERAH PERTANIAN LAHAN KERING KABUPATEN GUNUNGKIDUL - Eka Handayanta; Lutojo Lutojo; Kurniasih Nurdiati (Caraka Tani: Journal of Sustainable Agriculture, 2017)
This research was conducted to know the production efficiency of beef cattle in smallholder farmer in a dry farming area at dry season. Research has been started on June and finished on September (dry season) at smallholder farmer in the village Kemejing, Semin subdistrict, district Gunungkidul, DIY. The research materials are 28 heads of beef cattle from 17 farmers, which consist of 10 heads of PO breed, 10 heads of a Simpo breed, and 8 heads of Limpo breed with 292.25 kg of initial body weight. This research was using Participatory Rural Appraisal method which is a collecting data process that an active teamwork between data collector and farmer. Collected parameter are feed intake, average daily gain (ADG), feed efficiency, feed cost per gain (FC/G), and income over feed cost (IOFC). Data resulting from this research are 8.42 kg/head/day of feed intake, 0.19 kg/head/day of ADG, 0.021 of feed efficiency, Rp 46.166,62 of feed cost per gain, and Rp 3.985,55 of income over feed cost. It can be concluded that the efficient production of beef cattle in smallholder farmer at the dry area is low because average daily gain, feed cost per gain and income over feed cost produced are extremely small so if the calculated economic result is less favorable.